Social impact bonds: The securitization of the homeless. (November 2016) - Cooper, Christine; Graham, Cameron; Himick, Darlene
Abstract: This paper examines the recent phenomenon of social impact bonds (SIBs). Social impact bonds are an attempt to marketize/financialize certain contemporary, intractable "social problems", such as homelessness and criminal recidivism. SIBs rely on a vast array of accounting technologies including budgets, future cash flows, discounting, performance measurement and auditing. As such, they represent a potentially powerful and problematic use of accounting to enact government policy. This paper contains a case study of the most recent in a series of SIBs, the London Homelessness SIB, focusing on St Mungo's, a London-based charitable foundation that was one of two service providers (charities) funded by the SIB. The case study is intended to enable a critical reflection on the rationalities that underpin the SIB. For this purpose, the paper draws upon Michel Foucault's work on biopolitics and neoliberalism. The SIB is thoroughly neoliberal in that it is constructed upon an assumption that there is no such thing as a social problem, only individuals who fail. The SIB transforms all participants in the bond, except perhaps the homeless themselves, into entrepreneurs. The homeless are instead "failed entrepreneurs" who become securitized into the potential future cash flows of investors.